2021
DOI: 10.1038/s41419-021-03570-6
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signaling mediates the abnormal osteogenic and adipogenic capabilities of bone marrow mesenchymal stem cells from chronic graft-versus-host disease patients

Abstract: Chronic graft-versus-host disease (cGVHD) is the main cause of non-relapse mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Mesenchymal stem cells (MSCs) in bone marrow (BM) remain unclear in the pathophysiology of cGVHD. In this study, we analyzed BM-MSCs from 66 patients after allo-HSCT, including 33 with active cGVHD and 33 without cGVHD. BM-MSCs showed similar morphology, frequency, phenotype, and proliferation in patients with or without cGVHD. MSCs from the active cGVHD gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…For the downregulated DEGs, pathway enrichment analysis revealed that the graft-versus-host disease (GVHD) was significantly enriched. Qi et al [ 33 ] revealed that the adipogenic differentiation capacity was decreased in the active chronic GVHD MSCs compared with no-cGVHD MSCs. The adipogenesis of MSCs may be negatively associated with GVHD disease, which was in line with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For the downregulated DEGs, pathway enrichment analysis revealed that the graft-versus-host disease (GVHD) was significantly enriched. Qi et al [ 33 ] revealed that the adipogenic differentiation capacity was decreased in the active chronic GVHD MSCs compared with no-cGVHD MSCs. The adipogenesis of MSCs may be negatively associated with GVHD disease, which was in line with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…DKK3 has been reported to be secreted by MSCs, which have been shown to limit immune responses, including GVHD, by multiple soluble factors. Since DKK3 also regulates Wnt signaling ( 42 ), and Wnt/β-catenin signaling mediates increased osteogenic capacity and decreased adipogenic capacity in MSCs from patients with cGVHD MSCs ( 52 ), it is possible that DKK3 marks an early modulation of MSCs function toward a less regulatory phenotype. Thirdly, for alloreactive T cells to infiltrate target tissues, they have to migrate through the extracellular matrix (ECM).…”
Section: Discussionmentioning
confidence: 99%